Crown Vic [videorecording (DVD)] - Souza, Joel, 1973-; Jane, Thomas; Krumholtz, David, 1978-; Moynahan, Bridget, 1972- (Screen Media Films, 2020)
During one night's patrol, a veteran cop and his rookie partner chase down violent suspects while searching for a missing girl, all the while hunting two cop killers in Los Angeles.